Solution to problems in structural steel design to BS 5950:Part 1: 2000 - Osman, Mohd. Hanim (Penerbit UTM, 2008)
The aim of this book is to provide students and practicing engineers with a guide of structural steel design to meet the requirement of BS 5950:Part 1: 2000 Structural Use of Steelwork in Building. The emphasis has been to illustrate the clauses in the code rather than to match practical cases exactly. The first part of the book gives basic design concepts of structural elements comprising beam, column, connection, roof truss, and plate girder. In the second part, it presents worked examples of design of structural steel elements which are of commonly used in building frame structures. The examples have different design problem, which require different approach of loading analysis and design formula.